flamenco, a gene controlling the gypsy retrovirus of Drosophila melanogaster. - Prud'homme, N.; Gans, M.; Masson, M.; Terzian, C.; Bucheton, A. (Genetics, 1995)
Gypsy is an endogenous retrovirus of Drosophila melanogaster. It is stable and does not transpose with detectable frequencies in most Drosophila strains. However, we have characterized unstable strains, known as MG, in which it transposes at high frequency. These stocks contain more copies of gypsy than usual stocks. Transposition results in mutations in several genes such as ovo and cut. They are stable and are due to gypsy insertions. Integrations into the ovoD1 female sterile-dominant mutation result in a null allele of the gene and occurrence of fertile females. This phenomenon, known as the ovoD1 reversion assay, can be used to quantitate gypsy activity. We have shown that the properties of MG strains result from mutation of a host gene that we called flamenco (flam). It has a strict maternal effect on gypsy mobilization: transposition occurs at high frequency only in the germ line of the progeny of females homozygous for mutations of the gene. It is located at position 65.9 (20A1-3) on the X chromosome. The mutant allele present in MG strains is essentially recessive. Flamenco seems to control the infective properties of gypsy.